Empiricism, perceptual knowledge, normativity, and realism essays on Wilfrid Sellars - DeVries, Willem A., 1950- (Oxford : Oxford University Press, 2009)
These essays were written to celebrate the 50th anniversary of the lectures which became Wilfrid Sellars's 'Empiricism and the Philosophy of Mind', one of the crowning achievements of 20th century analytic philosophy. Both appreciative and critical they engage with his treatment of crucial issues in metaphysics and epistemology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sellars, Wilfrid